The Kelayakan Finansial Pendirian Bisnis Sosis Sapi PT XYZ di Kota Bogor, Jawa Barat, Indonesia - P Gandhi; I S Purwana (PETERPAN (Jurnal Peternakan Terapan), 2023)
Sausage products are one of the most popular animal-based foods that considerably contribute to daily human protein needs. As a positive response, PT XYZ, one of the meat processors in Bogor City, plans to establish a beef sausage business. The purpose of the study was to determine the financial feasibility of the proposed business by PT XYZ. Financial feasibility was based on cash flow analysis, profit and loss analysis, and business feasibility analysis. The latter was evaluated based on Net Present Value (NPV), Gross B/C, Net B/C, Internal rate of return (IRR), and payback period indicators. The proposed business showed NPV IDR 67,019,684.22, Gross B/C, of 1.03, a Net B/C of 3.14, an IRR of 66%, and a payback period of 2 Years. The beef sausage business proposed by PT XYZ was financially feasible in regard to those parameters.